Self-Silencing, but Not Sexual Relationship Power Associated with Condom Use for Black College-Aged Women - Lynissa R. Stokes; Leslie R. Brody (Behavioral Sciences, 2019)
Black adolescent and young adult women in the United States experience a disproportionately higher rate of HIV infections than White and Hispanic adolescent and young adult women. Heterosexual sexual activity is the main route of infection for women, regardless of race or ethnicity. We examined two potential barriers to reducing Black adolescent and young adult women’s HIV risk: high levels of self-silencing and low levels of sexual relationship power. Data were collected on a small convenience sample of sexually active Black college-aged women (N = 57, Mage = 19.6, SD = 1.4) who answered questions about their current or most recent dating relationship. We found that higher levels of self-silencing were significantly related to lower condom use frequency and to a lower likelihood of reporting condom use at last sex. No significant associations were found between sexual relationship power and condom use (frequency or at last sex). Data from this study suggest that self-silencing, which involves putting the needs of others ahead of one’s own in order to avoid conflict in relationships, is an important variable to consider when examining potential risk factors for sexually transmitted HIV among Black college-aged women. Implications for future studies on HIV risk are reviewed.